APLIKASI MEDIA PEMBELAJARAN e-ASEAN PADA MATERI IPS KELAS VI DI SEKOLAH DASAR - Zahroh As Sakinah; Aan Hendrayana; Rudi Hariyadi (STKIP Subang, 2023)
In the current era of rapid technological progress, there are still many learning processes that only use books as the only source of learning information. Thus, the learning process does not provide interesting or valuable experiences for students. Such a learning process will be easier for students to forget, because what they learn is part of a conventional learning process which is carried out in one direction where students do two activities at once, namely listening and taking notes. This learning is conventional learning that has been used for a long time (Djafaar, 2001:86). In this case, one of the materials in class VI which has quite a large and extensive quantity of discussion is material regarding ASEAN. ASEAN material is included in the social studies material group in class VI elementary school. ASEAN material covers the diversity of history, economics, politics, culture and geographical conditions of each ASEAN country. Seeing the abundance and breadth of ASEAN material that students need to learn, e-ASEAN Interactive learning media was developed. The aim of creating e-ASEAN learning media is to provide learning media about ASEAN that can be accessed via laptops or devices, so that the learning process is more interesting and easy to do. This e-ASEAN interactive learning media was created using a link-based PDF, which in the design process used the Canva application.